Multicomponent Interventions to Enhance Influenza Vaccine Delivery to Adolescents - Gargano, Lisa M. (American Academy of Pediatrics, 2011)
OBJECTIVE: To compare school- versus provider-based approaches to improving influenza vaccination coverage among adolescents in rural Georgia. METHODS: We used a nonrandomized, 3-armed design: (1) a middle- and high school-based influenza vaccination intervention in 1 county; (2) a provider-based influenza vaccination intervention in a second county; and (3) a standard-of-care condition in a third county. Interventions also included distribution of an educational brochure, school presentations, and community-based outreach to enhance vaccine knowledge and awareness among adolescents and their parents. RESULTS: During the 2008–2009 influenza season, 70 (19%) of 370 students were vaccinated in the school-based county and 110 (15%) of 736 students were vaccinated in the provider-based county, compared with 71 (8%) of 889 students in the standard-of-care county (risk ratio [RR](school): 2.4 [95% confidence interval (CI): 1.7–3.2]; RR(provider): 1.9 [95% CI: 1.4–2.5]). During 2009–2010, seasonal influenza vaccination coverage was 114 (30.4%) of 375 of students in the school-based county, 122 (16.9%) of 663 of students in the provider-based county, and 131 (15.2%) of 861 students in the standard-of-care county (RR(school): 2.3 [95% CI: 1.9–2.9]; RR(provider): 1.2 [95% CI: 0.97–1.5]). CONCLUSIONS: Special efforts to promote influenza vaccination among rural, predominantly black students were associated with increased vaccination coverage. The school-based influenza vaccination intervention was associated with the highest levels of vaccination coverage. This study revealed the efficacy of school-based influenza education to improve vaccination rates among adolescents.